Leveraging Skype-based Webinars as an English Language Learning Platform - Arini Nurul Hidayati; Tenia Ramalia; Fuad Abdullah (AL-ISHLAH: Jurnal Pendidikan, 2021)
This present study reports 30 students' first learning experiences when using Skype in an English Language Teaching (ELT) webinar series. Since numbers of ELT webinars have been flourishing throughout the corona pandemic situation in 2020, the utilization of diverse online platforms to facilitate the events has also been growing. Skype, an online application released in 2003, was not widely used by the participants in this study as their synchronous virtual English Language Learning (ELL) platform. As a result, many of them were not familiar with this application. Underpinning Gibbs' reflective framework, this qualitative scrutiny documented the encountered shortcomings and advantages written in the participants' journal. This study's findings revealed that the Skype-based webinar provides opportunities to stimulate the students' learning motivation, broadens their insights, and offers enjoyable learning circumstances. Despite the opportunities, there were also some drawbacks concerning the lack of intelligibility which generates learning anxiety and technical issues concerning signal stability.